The impact of Involvement in CRM Initiative on Inter-functional Integration and Organizational Performance: Evidence from Pakistani Enterprises - Ashraf, Muhammad; ., Mohammad Asif Khan; ., Noor Ismawati Jaafar; ., Ainin Sulaiman (Information Management and Business Review, 2015)
Customer Relationship Management (CRM) is IT based system that manage customer long term relationship, and also inter-function relationship within the organization with the ultimate purpose of creating customer value by sharing concise, sufficient, accurate, reliable, and timely valuable information has greatly enhanced inter-functional integration (IFI) and organizational performance (OP). The purpose of this study is to examine the relationship among three constructs: 1) Involvement (IN) of marketing and IT departments in CRM initiative, 2) IFI, and 3) OP, and presents conceptual model based on this relationship in which involvement in CRM initiative can affect OP either directly or indirectly through IFI. Data collected based on online survey from 30 large companies in Pakistan are analyzed in accordance with research objectives by using correlation, descriptive statistics, simple linear regression and other statistical tools of SPSS. Research findings suggest that involvement in planning, implementation, and usage of CRM system has positive but no significant immediate effect on OP and instead that it improves OP via indirect significant and potential positive effect on IFI highlight the importance for management to endorse IFI and consider involvement of stakeholders in CRM initiative as enabler.